Química nos Anos Finais do Ensino Fundamental: Uma Análise das Dificuldades dos Professores de Ciências no Processo de Ensino e Aprendizagem - Moraes, Cinara Aparecida de (2023)
Teaching Chemistry Science requires considering a lot of abstraction and the use of models and theories which can generate, in students, difficulties in learning some contents, causing a certain rejection and, consequently, influencing the teaching and learning process. In addition, in most cases teachers who work with what is considered to be the student's first contact with this science in elementary school, are graduates of undergraduate degrees in Biological Sciences, and many of them study a very restricted set of contents related to Chemistry.Within this context this research aimed to understand some difficulties present in the process of teaching and learning Sciences, mainly regarding the chemical contents taught by Basic Education teachers, specifically in the last years of Elementary Education. The study also sought to analyze which chemical contents are present in this stage of schooling and the ones which are pointed out as possible difficulties faced by the teachers who teach these contents. Facing the research problem, its specificities and the subjects involved, the most appropriate methodological perspective is of a qualitative nature research. It is also an applied study and has a documentary research basis as it uses analysis of official documents for the discussion of the results obtained during the investigation. Data collection and analysis take place from the outcome from the analysis of documents and productions in the area and some questionnaires followed by interviews. First of all, the documentary analysis on the subject was developed to better understand it and support the analyses. Then, a questionnaire was applied to know the profile of these professionals and an interview was also carried out. Official documents were analyzed when it was possible to point out which Chemistry content(s) normally present conceptual and technical difficulties, the ones that are difficult to teach, in addition to highlighting how teachers have faced these difficulties in the classroom on a daily basis, as well as creating strategies to improve teaching. From the data obtained we can say that the difficulties pointed out, whether in the research of studies, theses and dissertations and even in the applied questionnaires and interviews, are somehow all related to the following categories: Teacher; Student; Curriculum; and Infrastructure.